(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article analyzes the theoretical and practical aspects of the cost of attracted resources and their impact on the profitability of commercial banks. The study examines the expenses related to attracting bank resources, their structure, maturity, and dependence on market conditions. Methods for calculating the nominal and real cost of attracted funds are proposed, and their importance in assessing the efficiency of banks’ active operations is substantiated. Practical calculations are carried out using the example of a branch of AT “Aloqabank”, and conclusions and recommendations are formulated to improve the efficiency of bank resource management.